Nanostructured, complex hydride systems for hydrogen generation - Robert A. Varin; Amirreza Shirani Bidabadi (AIMS Energy, 2015)
Complex hydride systems for hydrogen (H2) generation for supplying fuel cells are being reviewed. In the first group, the hydride systems that are capable of generating H2 through a mechanical dehydrogenation phenomenon at the ambient temperature are discussed. There are few quite diverse systems in this group such as lithium alanate (LiAlH4) with the following additives: nanoiron (n-Fe), lithium amide (LiNH2) (a hydride/hydride system) and manganese chloride MnCl2 (a hydride/halide system). Another hydride/hydride system consists of lithium amide (LiNH2) and magnesium hydride (MgH2), and finally, there is a LiBH4-FeCl2 (hydride/halide) system. These hydride systems are capable of releasing from ~4 to 7 wt.% H2 at the ambient temperature during a reasonably short duration of ball milling. The second group encompasses systems that generate H2 at slightly elevated temperature (up to 100 °C). In this group lithium alanate (LiAlH4) ball milled with the nano-Fe and nano-TiN/TiC/ZrC additives is a prominent system that can relatively quickly generate up to 7 wt.% H2 at 100 °C. The other hydride is manganese borohydride (Mn(BH4)2) obtained by mechano-chemical activation synthesis (MCAS). In a ball milled (2LiBH4 + MnCl2) nanocomposite, Mn(BH4)2 co-existing with LiCl can desorb ~4.5 wt.% H2 at 100 °C within a reasonable duration of dehydrogenation. Practical application aspects of hydride systems for H2 generation/storage are also briefly discussed.